Deliberative Stakeholder Engagement in Person-centered Health Research. (2nd January 2022) - Mitchell, Gordon R.; Hartelius, E. Johanna; McCoy, David; McTigue, Kathleen M.
ABSTRACT: Robust stakeholder engagement in health research requires broad communicative integration, not only of patients but also other stakeholders such as health system leaders, clinicians, and researchers. As patients' personal narratives tend to focus on their own health care experiences, it can be challenging to incorporate these perspectives at the health system level, where discussions often address technical issues such as strategies for aggregating and interpreting population-level data. The PaTH Health System Leaders Demonstration Project provides a case study to explore the potential usefulness of deliberative techniques for facilitating heterogeneous stakeholder engagement in what some sociologists of science call 'hybid forums.' Close textual analysis of the event transcript yields insight on how social learning motivates group opinion shifts in deliberative processes. Reconstruction of the event's narrative arc marks a path of 'dynamic updating' that manifests in group opinion change. Analysis of episodes where participants perform 'deliberative openness' lends qualitative nuance to previously reported process measure outcomes reflecting high participant satisfaction. Such inquiry helps address a gap in literature on stakeholder engagement in comparative effectiveness health research, sheds light on the understudied genre of 'empowered deliberation', and illustrates design principles and practices useful for upstream integration of stakeholder engagement in the research process.